2013
DOI: 10.1016/j.estger.2013.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Cuantificación del riesgo de incumplimiento en créditos de libre inversión: un ejercicio econométrico para una entidad bancaria del municipio de Popayán, Colombia

Abstract: Este documento aborda el estudio del riesgo de crédito como un objetivo de la regulación bancaria moderna,partiendo de la teoría económica hasta llegar a una aproximación cuantitativa concreta. En este sentido,se plantean 2 modelos econométricos para una institución bancaria representativa en la cartera de libreinversión en el municipio de Popayán, Departamento del Cauca (Colombia), con los cuales se logra demostrarque su cartera de libre inversión es de bajo riesgo, aun bajo ciertas características… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 32 publications
0
0
0
Order By: Relevance
“…Finally, it is common for financing to women to be less risky (Schreiner, 1999), as shown by the results for the EC12 portfolio. In a Colombian case study, Salazar (2013) found statistical significance in the variable categorizing the gender of borrowers, as did Bellante & Green (2004). These findings suggest that women are more risk-averse and their propensity to make risky decisions is lower.…”
Section: Default Risk In Microfinance Institutions: Case Of a Costa R...mentioning
confidence: 88%
“…Finally, it is common for financing to women to be less risky (Schreiner, 1999), as shown by the results for the EC12 portfolio. In a Colombian case study, Salazar (2013) found statistical significance in the variable categorizing the gender of borrowers, as did Bellante & Green (2004). These findings suggest that women are more risk-averse and their propensity to make risky decisions is lower.…”
Section: Default Risk In Microfinance Institutions: Case Of a Costa R...mentioning
confidence: 88%